It Was a Tribute to Architectural Quest: The Fate of Monuments of Constructivist Architecture in Smolensk - Valuyev, Demyan V (Actual Problems of Theory and History of Art, 2020)
The article concerns the monuments of the constructivist style architecture in Smolensk. Аt the turn of the 1920–1930s, when Smolensk was the center of the western region of the USSR, a number of administrative, industrial, and residential buildings was built in this style. However, these buildings, primarily because of the stinginess and laconism of the design, caused a mixed reaction from both ordinary citizens of Smolensk and from representatives of the local authorities. Some local architects also criticized them. Criticism intensified after the condemnation of Constructivism at the level of higher authority. After the World War II, constructivist buildings were often restored in the forms of neoclassicism. However, a number of constructivist monuments have survived to this day almost in their original form. They serve as unique evidence of the experiments in the cultural and social spheres that took place during the “great breakthrough”.